2005
DOI: 10.1203/01.pdr.0000156502.84909.bc
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Breathing or Mechanical Ventilation Alters Lung Compliance and Tissue Association of Exogenous Surfactant in Preterm Newborn Rabbits

Abstract: In preterm infants with respiratory distress syndrome, surfactant administration followed by immediate extubation to spontaneous breathing with nasal continuous positive airway pressure reduces the need for mechanical ventilation. With this treatment approach, repeated doses of surfactant are rarely indicated. We used a rabbit model to test the hypothesis that exogenous surfactant therapy followed by spontaneous breathing results in a more sustained initial treatment response compared with treatment followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 45 publications
2
44
0
Order By: Relevance
“…We have previously reported the impaired tissue association of exogenous surfactant in preterm rabbits after MV compared with spontaneous breathing. 5 This finding was associated with a lower dynamic compliance and evidence of surfactant inactivation and constitutes a possible explanation to an attenuated treatment response after surfactant administration followed by MV. These data demonstrate that the immediate improvement in oxygenation following INSURE was sustained over the 48 h following treatment, which may have contributed to the low requirement for surfactant re-treatment.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We have previously reported the impaired tissue association of exogenous surfactant in preterm rabbits after MV compared with spontaneous breathing. 5 This finding was associated with a lower dynamic compliance and evidence of surfactant inactivation and constitutes a possible explanation to an attenuated treatment response after surfactant administration followed by MV. These data demonstrate that the immediate improvement in oxygenation following INSURE was sustained over the 48 h following treatment, which may have contributed to the low requirement for surfactant re-treatment.…”
Section: Discussionmentioning
confidence: 91%
“…3,4 We have previously shown that in premature rabbits, surfactant administration followed by MV resulted in impaired treatment response and a greater degree of surfactant inactivation than surfactant treatment followed by spontaneous breathing. 5 Furthermore, MV has been implicated as the single most important risk factor for the later development of bronchopulmonary dysplasia (BPD). 6,7 Surfactant treatment of spontaneously breathing infants by transient intubation was first reported in 1990 in a study performed in Kuwait, where MV was not available at the time.…”
Section: Introductionmentioning
confidence: 99%
“…It is a surprising result that, despite lower deposition of surfactant in the lungs, oxygenation was similar between the lambs that received LISA and the intubated lambs. This may be caused by the fact that in spontaneous breathing animals, exogenous surfactant has a higher tissue association and leads to a higher dynamic lung compliance compared to the ventilated animals, as was shown in a rabbit model by Bohlin et al (16).…”
Section: Discussionmentioning
confidence: 97%
“…This catheter is stiffer than the feeding tube, being easier to guide it through the vocal cords under direct vision without using Magill's forceps [15][16][17][18]. The surfactant administration during a noninvasive respiratory support is associated with a better distribution of the surfactant, as shown in animal models [19].…”
Section: Introductionmentioning
confidence: 99%